Pengaruh Strategi Pemasaran Shopee Live Streaming pada Industri Fesyen Terhadap Keputusan Pembelian Konsumen di Bandung Raya - Rini Nur Halimah (Asosiasi Ahli Administrasi Indonesia, 2022)
In the continuously evolving era of online commerce, E-commerce, especially Shopee, has become a favored platform for participants in the fashion industry. The innovative feature of Shopee Live Streaming allows sellers to interact directly with consumers, enhancing the online shopping experience. Recent data indicates that Shopee reached 161 million visitors in May 2023, reaffirming its crucial role in the market. The purpose of this study is to explore the impact of Shopee Live Streaming marketing strategies in the fashion industry on consumer purchasing decisions in Bandung Raya. The research sample involves 120 respondents, Shopee consumers in Bandung Raya, who have actively viewed Shopee Live Streaming. The analysis methods include descriptive analysis, correlation, and multiple regression. Data collection was conducted by distributing questionnaires via social media to respondents who met the criteria. The research results show that the influence Shopee Live Streaming has a positive and significant influence on purchasing decisions, with an R Square of 45.3%. However, 54.7% of the variation in purchasing decisions is influenced by other factors not examined in this study. These findings provide valuable insights into the dynamics of Shopee Live Streaming marketing strategies in influencing consumer preferences amid the rapid growth of online commerce.